Physiological quality evaluation of bean seeds submitted to hydric deficit during flowering - Fiegenbaum, Valdir; dos Santos, Dora Suely Barbosa; Mello, Vera Delfina C.; Filho, Benedito Gomes dos Santos; Tillmann, Maria Ângela A.; da Silva, João Batista (Pesquisa Agropecuaria Brasileira, 1991)
In order to evaluate physiological quality of three cultivars of bean seeds (Phaseolus vulgaris L.) submitted to hydric stress during flowering, an experiment was conducted in greenhouse using the cultivars Turrialba-4, Rio Tibagi and Empasc 201-Chapecó. In the flowering stage, the plants were separated into two groups: one maintaining normal irrigation (control), and another without irrigation during 15 days and later reirrigation. The physiological quality of seeds was evaluated by germination percentage, vigour through first count emergence velocity index, dry weight of seedlings and roots, and total activity of acid phosphatase, weight of 100 seeds, concentration of soluble sugars, starch, soluble amino acids and soluble proteins. The content of soluble sugars in seeds were reduced by hydric stress. However, only the starch content was reduced in cultivars Turrialba-4 and Rio Tibagi. The dehydration during flowering did not reduce weight of seeds, vigour and soluble aminoacid content and soluble proteins. Therefore, no changes in physiological quality of seeds were observed.